MALAY HISTORICAL THOUGHT - Hussain Othman (Penerbit UTHM, 2009)
The historical awareness among Indonesians flourished long ago and precisely since the end of 1957. The first Indonesian seminar on history held in Jogjakarta during the same year stressed upon the importance of developing a national concept of history based on certain proper foundations. In Malaysia, however the and UTM. However, we believe that this book is also suitable to all historical awareness seemed to be dampened with many other social and political circumstances. In comparison, the awareness did not flourish prior to 1957. During which the Indonesians were already on the track, the Malaysians were unfortunately struggling to develop a new independent country. In fact, during those times the intellectual legacies of the British colonial were easily subscribed in order to understand the Malay history. As a result, numerous misunderstandings and misconceptions fabricated by colonial intellectual masterminds became rampantly widespread among thoughts of the Malays. This fact ultimately explained the relevance of this book to the Malay intellectual development in the present day.